ORGANISATIONAL CITIZENSHIP BEHAVIOUR AND HEALTHCARE EMPLOYEES’ TURNOVER INTENTION: A BIBLIOMETRIC ANALYSIS OF RESEARCH TRAJECTORIES IN THE 21ST CENTURY - Ahmad Rafeein Mohamad; Kalsom Ali; Khairunneezam Mohd Noor (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This bibliometric analysis investigates research trends in organisational citizenship behaviour and turnover intention within healthcare settings. The study reveals a notable increase in scholarly interest in these topics. The term “turnover intention” is a core keyword, highlighting researchers’ central focus on retention issues. The emergence of diverse keywords in recent publications reflects the evolving nature of research, incorporating various organisational and individual factors and expanding the understanding of the interplay between organisational citizenship behaviour and turnover intention. The analysis identifies the United States and China as dominant contributors to this field, with the highest number of publications and strong cross-national collaborations. However, weaker connections in some other nations suggest potential for future collaboration. The predominance of research in nursing-specific journals indicates a high engagement level among nursing professionals, which may limit the exploration of evidence from other healthcare disciplines. The lack of involvement from various healthcare fields and underrepresented regions points to missed opportunities for comparative studies. Future research should broaden its scope to include diverse healthcare professions, foster wider collaboration, and investigate the combined effects of organisational and individual factors on OCB and TI in healthcare context.